1991
DOI: 10.1007/bf00054304
|View full text |Cite
|
Sign up to set email alerts
|

Vegetables, fruit, and cancer. II. Mechanisms

Abstract: The epidemiologic literature on the relationship between vegetable and fruit consumption and human cancer at a variety of sites was reviewed systematically in Part I. It was concluded that consumption of higher levels of vegetables and fruit is associated consistently, although not universally, with a reduced risk of cancer at most sites, and particularly with epithelial cancers of the alimentary and respiratory tracts. Possible mechanisms by which vegetable and fruit intake might alter risk of cancer are addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
363
3
8

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 793 publications
(380 citation statements)
references
References 120 publications
6
363
3
8
Order By: Relevance
“…This association was, however, apparently not attributable to quercetin, as the intake was not associated with CVA incidence. In addition to quercetin, however, apples also include catechin and other compounds that may explain the associations (Steinmetz & Potter, 1991). Our study is thus at variance with an earlier study based on a small male population (Keli et al, 1996), which suggested the presence of a protective effect of¯avonoids stemming primarily from black tea.…”
Section: Discussioncontrasting
confidence: 84%
“…This association was, however, apparently not attributable to quercetin, as the intake was not associated with CVA incidence. In addition to quercetin, however, apples also include catechin and other compounds that may explain the associations (Steinmetz & Potter, 1991). Our study is thus at variance with an earlier study based on a small male population (Keli et al, 1996), which suggested the presence of a protective effect of¯avonoids stemming primarily from black tea.…”
Section: Discussioncontrasting
confidence: 84%
“…This may be due to the anti-carcinogenic action of other constituents, including carotenoids such as lycopene, beta-carotene and lutein, which are present in yellow-orange or dark-green leafy vegetables, or other micronutrients present in these foods. 11,21 With regard to fruit intake, the small number of smokers is likely to have affected the power of our study to detect a significant relationship; the odds ratio for the highest tertile does suggest the possibility of a substantial reduction in risk that is consistent with results for smokers in other studies. 11,13 Interestingly, recent results from a prospective investigation (the Nurses' Health Study) show a significant reduction in risk with the highest quintile of intake for total vegetables, but not fruit, among current smokers, whereas among never smokers, the highest tertile of fruit intake had a significant protective effect.…”
Section: Discussionsupporting
confidence: 67%
“…However, apart from carcinogens our diet also contains anticarcinogenic compounds, i.e. minor non-nutritive constituents of vegetables and fruits which are correlated with decreased cancer risk (6,25,26). From animal studies it has been suggested that these compounds may, at least in part, be effective by virtue of enhancing detoxification systems (6,7,22,26).…”
Section: Discussionmentioning
confidence: 99%